Classical and Nonclassical Symmetries of Nonlinear Differential Equation for Describing Waves in a Liquid with Gas Bubbles - N. A. Kudryashov; D. I. Sinelshchikov (Моделирование и анализ информационных систем)
A nonlinear differential equation is considered for describing nonlinear waves in a liquid with gas bubbles. Classical and nonclassical symmetries of this equation are investigated. It is shown that the considered equation admits transformations in space and time. At a certain condition on parameters, this equation also admits a group of Galilean transformations. The method by Bluman and Cole is used for finding nonclassical symmetries admitted by the studied equation. Both regular and singular cases of nonclassical symmetries are considered. Five families of nonclassical symmetries admitted by this equation are constructed. Symmetry reductions corresponding to these families of generators are obtained. Exact solutions of these symmetry reductions are constructed. These solutions are expressed via rational, exponential, trigonometric and special functions.